Improving Students' Creative Thinking Skills in Mathematics Through Solving Open-Ended Problems - Dessi Arifianti; Muhammad Baidawi (LP2M Universitas Ibrahimy, 2024)
This study aims to improve students' creative mathematical thinking skills through solving open-ended problems. The method used in this study is Classroom Action Research (CAR), which consists of several stages: planning, implementation, observation, and reflection. The research subjects were 36 students. The results obtained from this study are that learning by solving open-ended problems can improve students' creative mathematical thinking skills, but not all achievement indicators are met. In cycle I, one student who answered in the non-creative category was very much while only a few were in the fairly creative category. In the second cycle, there was a change where students who answered in the non-creative category decreased and students who responded in the fairly creative category increased.